Organizational ethnography studying the complexity of everyday life - Ybema,Sierk 1967-; Yanow, Dvora; Wels, Harry (Thousand Oaks, California SAGE, 2009)
"Organizational Ethnography brings contributions from leading scholars in organizational studies that help to develop an ethnographic perspective on organizations and organizational research. The authors explore the special problems faced by organizational ethnographers, from questions of gaining access to research sites to various styles of writing ethnography, the role of friendship relations in the field, ethical issues, and standards for evaluating ethnographic work."--Publisher description.
Studying everyday organizational life / Sierk Ybema ... [et al.] -- Ethnographic doing and writing. -- Getting going : organizing ethnographic fieldwork / Kees van der Waal. -- Ethnographic practices : from 'writing-up ethnographic research' to 'writing ethnography' / Michael Humphreys and Tony Watson. -- Reading and writing as method : in search of trustworthy texts / Peregrine Schwartz-Shea and Dvora Yanow. -- When the 'subject' and the 'researcher' speak together : co-producing organizational ethnography / Simon Down and Michael Hughes. -- Familiarity and 'stranger-ness'. -- Making the familiar strange : a case for disengaged organization ethnography / Sierk Ybema and Frans Kamsteeg. -- Zooming in and zooming out : a package of method and theory to study work practices / Davide Nicolini. -- From participant observation to observant participation / Brian Moeran. -- At-home ethnography : struggling with closeness and closure / Mats Alvesson. -- Researcher-researched relationships. -- Lies from the field : ethical issues in organizational ethnography / Gary Alan Fine and David Shulman. -- 'But I thought we were friends?' Life cycles and research relationships / Nic Beech ... [et al.] -- Critical action research and organizational ethnography / Chris Sykes and Lesley Treleaven. -- Beyond complicity : a plea for engaged ethnography / Halleh Ghorashi and Harry Wels. -- Annotated bibliography. -- Defining 'organizational ethnography' : selection criteria / Dvora Yanow and Karin Geuijen. -- Bibliography / Karin Geuijen.
Keywords: Organizational sociology; Applied anthropology; Business anthropology